The Role of the Big Five Personality Test to Understand Yourself in the Modern and Multicultural Era - Zubaidah, Zubaidah; Rahayu, Dania Riski; Silvir, Syifa Azzahra; Silvir, M. Habibullah (Yayasan Minang Darussalam, 2024)
In the midst of the ongoing development of globalization, the importance of understanding individual personality is increasingly significant. This article explores innovations in the BIG FIVE Test, which is a tool that has proven effective in evaluating personality dimensions such as openness, conscientiousness, extraversion (sociability), agreeableness, and tendency toward anxiety. With a more modern and relevant approach, this test not only helps individuals recognize themselves but also provides insights into interactions within a multicultural context. This article highlights how global factors, such as technological advancements, intercultural communication, and social changes, influence personality. The aim of this research is to emphasize the importance of adapting personality measurement tools to understand the complexities of individual identity in an increasingly interconnected world. It is hoped that the findings from this study can serve as a reference for professionals in psychology, education, and human resource development in creating more effective and inclusive programs.